A quantitative analysis of supply response in the Namibian mutton industry - Van Wyk, Daniel Nicolaas (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2011.